A calculus problem by Lenedel Bert Delfin

Calculus Level pending

What is the normal of the line tangent to f ( x ) = x 2 + 2 x + 1 f\left( x \right) ={ x }^{ 2 }+2x+1 at (0,0).

2x - y = 0 x - 2y = 0 2x+ y = 0 x + 2y = 0

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Daniel Barnhurst
Nov 19, 2014

The first step towards finding the normal line of the tangent line is, of course, to find the tangent line. To do this you must first find the slope by taking the derivative of the function.

d d x f ( x ) = d d x ( x 2 + 2 x + 1 ) = 2 x + 2 \frac{\mathrm d}{\mathrm d x} f(x) = \frac{\mathrm d}{\mathrm d x} (x^2 + 2x +1) = 2x + 2

Next, since the point is at ( 0 , 0 ) (0, 0) , you substitute in x = 0 x=0 .

f ( 0 ) = 2 ( 0 ) + 2 = 2 f'(0) = 2 * (0) + 2 = 2

So the slope of the tangent line is 2 2 . Substituting the slope and the point ( 0 , 0 ) (0, 0) into the point-slope form of a linear equation we get:

( y y 1 ) = m ( x x 1 ) (y - y_1) = m * (x - x_1) \to ( y 0 ) = 2 ( x 0 ) (y - 0) = 2 * (x-0) )

The normal to a line is the negative reciprocal of the slope, so in this case the normal to a slope of 2 2 is 1 2 \Large -\frac{1}{2} . Substituting that into the point slope equation we get:

( y 0 ) = 1 2 ( x 0 ) y = 1 2 x 2 y = x x + 2 y = 0 (y - 0) = -\frac{1}{2} * (x - 0) \to y = -\frac{1}{2} * x \to 2 * y = -x \to x + 2 * y = 0

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...